Investigating the modulatory effects of Moringa oleifera on the gut microbiota of chicken model through metagenomic approach - Soundararajan, Sowmiya; Selvakumar, Jasmine; Maria Joseph, Zion Mercy; Gopinath, Yuvapriya; Saravanan, Vaishali; Santhanam, Rameshkumar (Frontiers in Veterinary Science, 2023)
In this study, metagenomics analysis has been used to perform a preliminary examination to determine the effects of adding Moringa oleifera leaf powder as a phytobiotic supplement on the chicken gastrointestinal microbiota. One-day old (n=40) fourty chickens were fed according to their basal requirements for 42 days and separated into two treatments as 0% phytobiotic provision normal basal diet (SG1) and 10% Moringa oleifera leaf powder (SG2). Metagenomics study revealed operational taxonomic units (OTUs) clustering, species annotation, and biodiversity. Alpha and Beta diversity showed both richness and relative abundance between the groups. Comparing the MOLP group (SG2) to the typical control group, the metagenomics data showed a 47% rise in Bacteroides and a 30% decrease in Firmicutes, Proteobacteria, Actinobacteria, and Tenericutes (SG1). In the treatment group, TM7 bacteria that were not present in the control group were found. The isolated unidentified bacteria were subjected to 16S rRNA sequencing for molecular characterisation, and the sequences were submitted under NCBI Accession Number: PRJNA823890. Additional results-based isolation of the described -bacteria from the chicken gut treated with MOLP were tested for essential metabolites. The antibacterial, antioxidant, and anticancer activities of the metabolites seemed encouraging. According to the research, Moringa oleifera enhances the gut microbiota in chicken models by acting as a modulator. The modulatory role of the phytobiotic in chicken models was confirmed by PICRUSt analysis, which discovered that carbhohydrate and lipid metabolism were increased in the phytobiotic (MOLP) treated gut microbiota.